Diversity of medicinal plants and their therapeutic usages of Kachin people (Jinghpaw) in the central part of Kachin State, Myanmar. (10th February 2023) - Hein, Pyae Phyo; Arunachalam, Karuppusamy; Fu, Yao; Zaw, Moe; Yang, Yongping; Yang, Xuefei
Abstract: Ethnopharmacological relevance: The traditional medical system plays a major role in healthcare in Kachin State, Myanmar, where long-term political instability persists and conventional healthcare facilities are inadequate. A knowledge of the traditional medicinal plants therefore benefits the Kachin people, yet documentation and records of the uses of these plants are rare. In this study, we attempt to answer the questions on what medicinal plants and how they are used by the Kachin people. Aim of the study: We aimed to document knowledge of the traditional medicinal plants and to identify those most frequently used by the Kachin people. Materials and methods: Eighty-two informants from eight villages in three townships were interviewed, and their knowledge of medicinal plants was recorded. The reported ailments were classified to the standard categories of the International Classification of Primary Care-2 (ICPC-2) system. Use reports (UR) were employed to evaluate the knowledge consensus of the informants. Results: We recorded a total of 117 species used as medicinal plants, of which 22 are newly recorded medicinal plant species for Myanmar. The plants belonged to 103 genera in 52 families, and were used to treat a total of 72 ailments from 17 ICPC-2 disease categories. Fabaceae and Lamiaceae were the most highly represented families of medicinal plants, with eleven and eight species used, respectively. The most cited species based on URs were Tinospora cordifolia (Willd.) Hook.f. & Thomson (URs = 39), Oroxylum indicum (L.) Kurz (URs = 28), Aquilaria malaccensis Lam. (URs = 26), Chromolaena odorata (L.) R.M.King & H.Rob. (URs = 24), and Chloranthus elatior Link. (URs = 22). Digestive system disorder was the most prevalent disease category, and was treated with 47 different medicinal plants (URs = 142). Leaves were the most commonly used plant part; decoction was the dominant method of preparation; and oral consumption was the most frequent method of administration. Conclusion: Our study documented a list of 117 medicinal plants and their uses in traditional medicine based on the local knowledge of the Kachin people. The study also identified the five most frequently cited species and found that the plants investigated are used to treat a total of 72 diseases. The 642 therapeutic reports we collected showcase a rich and diverse living knowledge of medicinal plant use by the Kachin people. Moreover, we present 22 new medicinal records, enriching the list of known medicinal plants in Myanmar. This exploratory study has enabled us to assemble the local knowledge of the Kachin people into solid dataset that will allow further scientific validation and will potentially contribute to better integration of medicinal plants into the healthcare provision for Kachin people in Myanmar. Graphical abstract: Image 1 Highlights: The Kachin people's usage of medical plants is documented, and the list of medicinal plants in Myanmar has been added. The research paves the way for medicinal plants' knowledge of the Kachin people and their therapeutic applications. The study provides insights into how the Kachin people interact with medicinal plant resources and healthcare problems.